2010
DOI: 10.1016/j.ijsolstr.2010.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of fracture in a cast aluminium alloy

Abstract: a b s t r a c tThis paper describes an experimental and numerical investigation on the fracture behaviour of a cast AlSi9MgMn aluminium alloy. In the experiments, a modified Arcan test set-up was used to study mixed-mode fracture. During testing, the tension load and the displacement of the actuator of the test machine were recorded, simultaneously as a high-resolution digital camera was used to record a speckle-patterned surface of the specimen. The recorded images were post-processed using an in-house digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…using a fracture criteria [18] or a damage evolution model [19]. Homogeneous material behaviour with local values in amount and effect of defects have typically been used to simulate local variations in material performance [20,21] and stochastic methods have been applied to consider the effect of defects on damage [22] or failure [23] of cast components. Previous investigations regarding the effect of local variations in mechanical behaviour on the mechanical behaviour of components, however, have not been found in the literature.…”
Section: Effect Of Homogeneous Mechanical Behaviourmentioning
confidence: 99%
“…using a fracture criteria [18] or a damage evolution model [19]. Homogeneous material behaviour with local values in amount and effect of defects have typically been used to simulate local variations in material performance [20,21] and stochastic methods have been applied to consider the effect of defects on damage [22] or failure [23] of cast components. Previous investigations regarding the effect of local variations in mechanical behaviour on the mechanical behaviour of components, however, have not been found in the literature.…”
Section: Effect Of Homogeneous Mechanical Behaviourmentioning
confidence: 99%
“…Regarding cast materials, DIC has e.g. been applied on a microstructural level to study the distribution of strain over different phases during tensile loading of cast irons [26] and on a macroscopic level to study the fracture of a HPDC aluminium alloy [27]. However, the use of DIC to characterise or investigate the macroscopic effects of local variations in microstructure caused by local variations in solidification conditions has not, to the authors' knowledge, been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The Cockcroft-Latham fracture criterion is convenient to use since it is based on only one parameter, Wc, that can be determined from a single test. 57 The fracture criterion is rewritten as an ISV damage evolution law for the damage variable D according to 58 …”
Section: The Fc-methodsmentioning
confidence: 99%
“…The FC method has been used to study the effect of statistical variations of mechanical behaviour in a component. 58 The probability of particle fracture, ppf(W), was assumed to follow a Weibull distribution as 58,59 …”
mentioning
confidence: 99%